Peningkatan Kinerja Operasi Dan Pemeliharaan Jaringan Irigasi Pacal Kabupaten Bojonegoro, Jawa Timur - Cynthia Rahma Dewi; Eko Andi Suryo; As’ad Munawir (Department of Civil Engineering, Faculty of Engineering, University of Brawijaya, 2017)
Pacal Irrigation is an infrastructure that services most agricultural areas in Bojonegoro City, East Java. Some problems has been found in this facillities such as misdistribution of water, inadequate condition of facilities, illegal oulet canals, and non conformity in operation and maintenance (OM)procedures. This study aims to determine existing condition, main affecting factors and improving strategy of operational and maintenance at the Pacal Irrigation. Primary data was used in this study gathered from questionnaires of 93 respondents and 8 experts in Irrigation Management Study Area. Descriptive analysis was used to explain the existing condition of OM performance of Pacal Irrigation. Important Performance Analysis (IPA) method was applied to determine the main priority factors affecting OM Performance. Furthermore, the SWOT method then was used to define strategies for improving OM performance of PACAL Irrigation. The results of the IPA analysis show there are 11 main prioroty factors affecting OM performance of PACAL Irrigation network. Furthermore, from SWOT Analysis it can be suggesteded that the “growth” strategy can be applied at Pacal Irrigation.